Advances in research based on antibody-cell conjugation - Ma, Xiaoxuan; Jiang, Jian; An, Xiaoye; Zu, Wanting; Ma, Chi; Zhang, Zhuo; Lu, Yaci; Zhao, Lijing; Wang, Lisheng (Frontiers in Immunology, 2023)
Antibody-cell conjugation (ACC) technology is a new research direction in medicine and biotechnology in recent years. The concept of ACC was proposed by Jie Li et al in 2018 and developed into a viable cell therapy technology, which refers to the cells with specific functions. Such as natural killer cells (NK cells), cytokine induced killer cells (CIK) and other immune cells and monoclonal antibodies through the linker together formed conjugate. ACC directly modifies specific antibodies on the cell surface through a simple and effective chemical coupling method to enable cells to have new functions. ACC has been developed for the treatment of various diseases, including cancers of the blood system and solid tumors. This paper reviews the current ACC construction methods, challenges and future development directions.